Trans-Septal Myocardial Biopsy in Hypertrophic Cardiomyopathy Using the Liwen Procedure: An Introduction of a Novel Technique - Chao Han; Mengyao Zhou; Rui Hu; Bo Wang; Lei Zuo; Jing Li; Shengjun Ta; David H. Hsi; Jiani Liu; Lichun Wei; Liwen Liu (Journal of Interventional Cardiology)
Objective. The purpose of this study was to evaluate the feasibility and safety of myocardial biopsy using a new approach, the Liwen procedure. Background. Myocardial biopsy is essential when other methods could not differentiate other etiologies from hypertrophic obstructive cardiomyopathy (HOCM). Our previous work using intramyocardial radiofrequency ablation for hypertrophic obstructive cardiomyopathy (Liwen procedure) may provide another approach to obtain the myocardial samples. Method. Seventeen patients with HOCM were enrolled for biopsies through percutaneously accessed intramyocardial septum and evaluated possible complications. Results. We obtained 31 specimens from 17 patients with a success rate of sample acquisition 100.0%. The number of myocardial samples taken per patient was 1.8 ± 0.8, and the average length of all samples was 16.7 ± 5.6 mm which could be used for pathological diagnosis. The complications included pericardial effusion with and without tamponade in one patient (5.9%), and no incidence of nonsustained and sustained ventricular tachycardia, conduction abnormity, perforation, stroke, and pneumothorax. The inhospital and 30-day mortality was 0%. Conclusion. This study has shown that myocardial biopsy of the Liwen procedure is relatively safe and technically feasible with adequate tissue sampling, which may help pathological diagnosis and further research of HOCM of diverse etiologies. This trial is registered with NCT04355260.